Walking the commonplaces of paradise: Pastoral precursors in Milton's garden of Eden. Issue 6 (1st November 2020) - Solomon, Deborah
ABSTRACT: This essay draws attention to the perambulatory nature of Milton's pastoral poetry. When read alongside the seventeenth century's changing horticultural tastes, his revisions of pastoral commonplaces indicate a garden-acculturated readership – one not only familiar with the celebrated walks found in chorographical reports and gardening manuals but also one keen on comparing real and literary descriptions of nature. In addition, Milton's use of pastoral modes shifts focus from the green space of the locus amoenus as a means of evoking a beloved body to the green space as a pleasurable end in itself. In this context, Paradise Lost reads as an origin story for the pastoral genre, an imagined precursor to the less innocent forms familiar to his readers. Ultimately, Milton's adapted pastoral commonplaces lead readers through a shared literary environment in a way that encourages multiple perspectives – not just of time and place but of creation and reception as well.